Potential of Pangi Leaf Extract For Papaya Mealybug Control (Paracoccus marginatus) - Juliet Merry Eva Mamahit; Vivi B. Montong; Sandra E. Pakasi (Jurnal Penelitian Pendidikan IPA, 2024)
The use of smer plant extracts is one alternative in environmentally friendly pest control. This research generally aims to obtain a technology for controlling Paracoccus marginatus mealybug pests that is environmentally friendly and easily applied by farmers. This study aims to determine the formulation of vegetable insecticide extract of pangi leaves to control papaya mealybug P. marginatus. This research was conducted at the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Sam Ratulangi University Manado. This research method used consisted of five treatments of pangi leaf extract dosage, namely: 5%, 10%, 20%, 40% and control. Each treatment was tested on pest nymphs. P. marginatus. And each treatment was repeated 5 times. The results of the study showed that 40% pangi leaf extract had the highest percentage of daily mortality at 24% and 48%. The higher the concentration of pangi leaf extract formulation, the higher the killing power on mealybug P. marginatus.